Governing a Pandemic: Assessing the role of collaboration on Latin American responses to the COVID-19 crisis - Cyr, Jennifer (2021)
How do governments address complex, cross-sectoral problems, like the COVID-19 pandemic? Why were some Latin American countries more successful at containing the pandemic´s most devastating health outcomes? We argue that national governments that were more collaborative in their response to COVID-19 were more successful in reducing death rates. Our original dataset offers a novel attempt to operationalise collaborative governance (CG). We undertake simple statistical tests to measure the relationship between CG and COVID-19-related mortality rates in Latin America. We then choose three case studies to assess whether collaboration was meaningful in practice. Initial evidence suggests governments that pursued CG were more effective at containing mortality rates early on in the pandemic. The collaboration helped to foster cooperation over resources; buy time to prepare for a potential case surge; and produce a unified message regarding what citizens should do to prevent viral spread.